STRATEGI KERJASAMA PENTAHELIX PENELITIAN DAN PENGEMBANGAN (LITBANG) ALUTSISTA DALAM PEMENUHAN KEBUTUHAN POKOK TNI (STUDI KASUS DI PT.PINDAD-BANDUNG) - Novi Herdian; Marsono; Herlan Budi Hermawan (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
This study aims to analyze the pentahelix collaboration strategy in research and development (R&D) of defense equipment as an effort to meet the essential needs of the Indonesian National Army (TNI), using PT Pindad in Bandung as a case study. The pentahelix approach involves collaboration among government, academia, industry, society, and media, which is expected to create an effective innovation ecosystem that responds to the country's defense needs. Through an in-depth analysis of the cooperation established between PT Pindad and related stakeholders, this research identifies the strengths, challenges, and opportunities in the development of defense equipment. The findings indicate that the synergy among various stakeholders not only enhances the quality of military products but also reinforces Indonesia's overall defense resilience. Therefore, the pentahelix collaboration strategy can serve as an effective model for future defense equipment development efforts